Lawig kalinaw mga sugilanon sa pagpanday og kalinaw sa katilingban = Peace journey : stories of peacebuilding efforts in the communities - Timonera, Bobby (Balay Mindanaw Foundation, 2010)
Collection of stories of 16 peace builders in rural Misamis Oriental and of a Higaunon datu in neighboring Agusan del Norte.